2009
DOI: 10.1007/s00424-009-0703-x
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3 in keratinocytes transmits temperature information to sensory neurons via ATP

Abstract: Transient receptor potential V3 (TRPV3) and TRPV4 are heat-activated cation channels expressed in keratinocytes. It has been proposed that heat-activation of TRPV3 and/or TRPV4 in the skin may release diffusible molecules which would then activate termini of neighboring dorsal root ganglion (DRG) neurons. Here we show that adenosine triphosphate (ATP) is such a candidate molecule released from keratinocytes upon heating in the co-culture systems. Using TRPV1-deficient DRG neurons, we found that increase in cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
207
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(211 citation statements)
references
References 40 publications
2
207
1
1
Order By: Relevance
“…These findings strongly support the hypothesis that trigeminal neurons receive environmental signals indirectly by transmission from adjacent cells in their peripheral innervation area. Previous studies have shown that mechanical and thermal stimulation of skin cells also leads to the release of ATP, which subsequently activates trigeminal neurons (27,45). This result is strongly indicative for similar processing mechanisms and a general skin-nerve communication.…”
Section: Discussionsupporting
confidence: 53%
“…These findings strongly support the hypothesis that trigeminal neurons receive environmental signals indirectly by transmission from adjacent cells in their peripheral innervation area. Previous studies have shown that mechanical and thermal stimulation of skin cells also leads to the release of ATP, which subsequently activates trigeminal neurons (27,45). This result is strongly indicative for similar processing mechanisms and a general skin-nerve communication.…”
Section: Discussionsupporting
confidence: 53%
“…TRPV3 and TRPV4 (12,13), both of which are expressed in skin keratinocytes, could have distinct roles because they are activated by a similar range of temperatures in the same type of cells. Indeed, TRPV3 is primarily involved in warm temperature-evoked ATP release from keratinocytes (14), and its mutation causes abnormality in hair growth and allergic dermatitis in the skin (15,16). On the other hand, we found that TRPV4, but not TRPV3, associates with the AJ complex (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Because both TRPV3 and TRPV4 are expressed in keratinocytes and are activated by a similar range of temperatures, these channels likely have distinct functions in the skin. Consistent with this idea, a recent report provided evidence that TRPV3, rather than TRPV4, mainly participates in transmission of warm temperature information from keratinocytes to adjacent nerve endings through ATP release (14). It has also been reported that mutation of TRPV3 is linked to defective hair growth and dermatitis in rodents (15,16), although the involvement of TRPV4 has not been confirmed.…”
mentioning
confidence: 97%
“…Keratinocytes may directly transduce thermal stimuli via warmth-activated TRP channels, TRPV3 (with an apparent threshold of about 32-39 C) and TRPV4 (27-34 C). [2][3][4] Nevertheless, it is important to note that at ambient temperatures from C10 C to C30 C, the unprotected human skin temperature settles at mean steady-state values within the range of C24 C to C33 C, respectively, 5 which is within the functional range of TRPM8 cold sensitivity. 6,7 Yet, the molecular identification of the cold transducer which translates cooling into downstream signaling events in keratinocytes was lacking.…”
Section: Introductionmentioning
confidence: 92%